Gradient pore porous tantalum carbide ceramic for silicon carbide single crystal growth and preparation method thereof
Patent Information
- Application Number
- CN202611404501.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-16
AI Technical Summary
[0007]本发明针对现有技术中多孔碳化钽陶瓷难以同时兼顾低气体流阻、颗粒过滤能力、气流均化效果及整体结构稳定性的技术问题,提供一种用于碳化硅单晶生长的梯度孔多孔碳化钽陶瓷及制备方法
[0030] Compared with existing technologies, this invention sets up a large-pore region, a transition pore region, and a small-pore region with successively decreasing pore size and porosity along the gas phase transport direction. The large-pore region effectively reduces gas entry resistance, the small-pore region efficiently blocks SiC dust and particles, and the transition pore region achieves a smooth transition in pore size and porosity, thus balancing low gas flow resistance and high particle filtration capability. At the same time, the gradient distribution of pore size and porosity allows the gas phase components to be gradually dispersed and homogenized during the passage of the porous component, effectively improving the uniformity of gas phase component distribution on the seed crystal surface. In addition, by setting mixed transition materials between adjacent pore structure regions and combining integral pressing and integrated sintering to form a continuously connected tantalum carbide skeleton, the interlayer shrinkage difference and abrupt pore structure changes are significantly reduced, avoiding delamination, warping, and cracking, and improving the integrity and high-temperature structural stability of the component. This preparation method does not require complex templates or multiple independent sinterings, the process is simple and flexible, and can be customized for different PVT furnace sizes and process requirements, making it suitable for long-term service in high-temperature silicon-containing atmospheres.
Smart Images

Figure CN122916716A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of porous ceramic material preparation technology, specifically relating to a gradient-pore porous tantalum carbide ceramic for silicon carbide single crystal growth and its preparation method, which is particularly suitable for gas phase transport control, gas flow homogenization and particle filtration in the process of growing silicon carbide single crystals by physical vapor transport method. Background Technology
[0002] Silicon carbide single crystals are primarily grown using the physical vapor transport (PVT) method. At temperatures above 2000℃, silicon carbide powder sublimates to form a gaseous component, which is then transported and deposited from the powder region to the seed crystal region. The gas flow distribution within the furnace, the resistance to gas transport, and particle migration directly affect the material supply to the seed crystal surface and the crystal growth quality. Existing research indicates that placing porous components between the powder source and the seed crystal can regulate the gas transport and powder sublimation process. Tantalum carbide (TaC) possesses characteristics such as a high melting point (approximately 3880℃), high-temperature resistance, and good chemical stability. Fabricating porous components from TaC can be used for gas guidance, gas flow homogenization, and particle blocking within the PVT furnace.
[0003] However, existing porous tantalum carbide ceramics have the following technical problems in practical applications: (1) It is difficult to balance gas flow capacity and particle filtration capacity. Existing porous tantalum carbide ceramics usually adopt a uniform pore structure. When the pore size is large and the porosity is high, the gas flow resistance is small, but the interception capacity of silicon carbide dust, graphite particles and gas phase condensed particles is insufficient. When the pore size is small and the porosity is low, although the filtration effect is better, the gas flow resistance increases significantly, which will significantly affect the gas phase transport during the PVT growth process.
[0004] (2) Uniform hole structure makes it difficult to achieve uniform airflow control. During the growth of silicon carbide single crystal PVT, there are differences in temperature, gas flow rate and gas phase flux at different locations in the furnace. The gas flow capacity of each region of the traditional uniform hole structure is basically the same, making it difficult to make targeted adjustments to the local airflow. This can easily lead to concentrated or uneven airflow distribution, affecting the uniform transport of gas phase components on the seed crystal surface.
[0005] (3) Different pore structure regions are prone to delamination and cracking. When gradient porous ceramics are prepared using different particle sizes and addition amounts of pore-forming agents, the shrinkage degree of each region is different during degreasing, carbothermic reduction and high-temperature sintering processes. This can easily lead to the formation of obvious interfaces between layers, resulting in delamination, warping and cracking, which affect the overall strength and high-temperature stability of the components.
[0006] In the prior art, some related patents have disclosed methods for preparing porous tantalum carbide ceramics or gradient porous ceramics. For example, CN121318523A discloses a gradient sintering preparation method for porous tantalum carbide plates, which uses a gradient forming technique to form a multi-layer green body by mixing tantalum carbide and tantalum disilicide powders; CN120441340B discloses a high-strength porous ultra-high temperature carbide ceramic with a stepped pore size distribution and its preparation method, which obtains a gradient pore structure by layering and pressing sintering pore-forming agents of different particle sizes; CN107673760A discloses a method for preparing gradient porous ceramics by layering and stacking. However, these prior art technologies all have their own shortcomings and have not yet been able to solve the above three technical problems simultaneously. Summary of the Invention
[0007] This invention addresses the technical problem in existing porous tantalum carbide ceramics that are difficult to simultaneously achieve low gas flow resistance, particle filtration capability, gas flow homogenization effect, and overall structural stability. It provides a gradient-pore porous tantalum carbide ceramic for silicon carbide single crystal growth and its preparation method.
[0008] To achieve the above objectives, the present invention provides a method for preparing gradient-pore porous tantalum carbide ceramics for silicon carbide single crystal growth, the method comprising the following steps: S100. Using tantalum pentoxide powder as the tantalum source and carbon powder as the carbon source, pore-forming agents with different particle sizes and different amounts are added to prepare a mixture of at least three different pore structure regions. As the pore size of different pore structure regions decreases, the particle size and amount of the pore-forming agent added accordingly decrease sequentially.
[0009] The preferred pore structure region includes a macropore region, a transition pore region, and a micropore region with successively decreasing pore size; the molar ratio of tantalum pentoxide to carbon in the mixture is 1:7 to 1:10; the carbon powder can be one or more of carbon black, graphite powder, or high-purity carbon powder.
[0010] The pore-forming agent can be one or more of PMMA microspheres, polystyrene microspheres, starch, and phenolic resin microspheres.
[0011] The parameters for the pore-forming agent in different pore structure regions are set as follows: The pore size of the pore-forming agent in the macroporous region of the mixture is 100-400 μm, and the amount of pore-forming agent added is 25%-40% of the total mass of tantalum pentoxide powder and carbon powder in the mixture. The transition pore zone corresponds to a pore-forming agent particle size of 50–200 μm in the mixture, and the amount of pore-forming agent added is 15%–30% of the total mass of tantalum pentoxide powder and carbon powder in the corresponding mixture; The pore size of the pore-forming agent in the mixture corresponds to a particle size of 10–100 μm, and the amount of pore-forming agent added is 5%–20% of the total mass of tantalum pentoxide powder and carbon powder in the mixture.
[0012] S200. Mix the mixtures of two adjacent pore structure regions at a mass ratio of 1:3 to 3:1 to obtain multiple interface transition materials.
[0013] The specific steps are as follows: Mix the macroporous zone mixture and the transitional pore zone mixture at a mass ratio of 1:3 to 3:1 to obtain the first interface transition material; The transition zone mixture and the small hole zone mixture are mixed at a mass ratio of 1:3 to 3:1 to obtain the second interface transition material.
[0014] By setting the interface transition material, the particle size, content and composition of the pore-forming agent gradually change between adjacent pore structure regions, reducing abrupt changes in interlayer pore structure and differences in sintering shrinkage.
[0015] S300. Following the decreasing order of pore size in different pore structure regions, the mixture and interface transition material are sequentially filled into the same molding die.
[0016] The specific steps are as follows: The filling is carried out in the following order: "large pore area mixture - first interface transition material - transition pore area mixture - second interface transition material - small pore area mixture", that is, the different interface transition materials are located between the mixtures of two adjacent pore structure regions.
[0017] In the process of partitioned filling, one of the following two methods can be used: (1) According to the order of decreasing pore size in different pore structure regions, the mixture and interface transition material are filled into the same molding mold in sequence. After the filling is completed, the overall unidirectional pre-pressing and cold isostatic pressing are carried out in sequence to form an integrated gradient pore blank. (2) According to the order of decreasing pore size in different pore structure regions, the mixture and interface transition material are filled into the same molding mold in sequence, and unidirectional pre-pressing (light pre-pressing) is performed after each mixture or interface transition material is filled into the molding mold until all filling is completed. Then, the overall unidirectional pre-pressing and cold isostatic pressing are performed in sequence to form an integrated gradient pore blank.
[0018] The unidirectional pre-compression pressure is 20–80 MPa, and the cold isostatic pressure is 100–250 MPa.
[0019] The proportion of the thickness of each region to the total thickness of the billet can be adjusted according to actual needs. Preferably, it is 25%–35% for the large hole region, 5%–15% for the first interface transition region, 15%–25% for the transition hole region, 5%–15% for the second interface transition region, and 25%–35% for the small hole region. The filler thickness of a single interface transition material accounts for 5%–15% of the total thickness of the gradient hole billet, and the filler thickness of a single interface transition material accounts for 25%–60% of the thickness of the transition hole region.
[0020] By pre-pressing the entire structure in one direction, the pore structure area and the interface transition area are initially compacted, the particles rearranged and the interface contacted in the axial direction. Then, cold isostatic pressing is performed so that the billet is subjected to relatively uniform pressure in all directions, which further improves the overall density and uniformity and the stability of the interface bonding, thus forming an integral billet without obvious separation interface.
[0021] S400. The gradient hole preform is placed in a vacuum or inert atmosphere for degreasing treatment to decompose and remove the pore-forming agent and organic additives. The heating rate of the degreasing treatment is 0.5-3℃ / min, the degreasing temperature is 400-600℃, and the holding time is 1-4h.
[0022] During the degreasing process, the heating rate should be controlled to avoid the rapid decomposition of the pore-forming agent, which would generate a large amount of gas and cause the green body to crack, bulge, or separate between layers.
[0023] S500. Under vacuum or flowing argon conditions, the degreased gradient pore blank is subjected to carbothermic reduction sintering treatment, so that tantalum pentoxide in the mixture undergoes carbothermic reduction reaction with carbon to generate tantalum carbide, thereby forming a continuously connected porous tantalum carbide skeleton between different pore structure regions, and obtaining a semi-finished product.
[0024] The carbothermal reduction sintering temperature is 1700~2100℃, the holding time is 1~5h, the pressure is 500~5000Pa, and the carbothermal reaction formula is: Ta2O5+7C→2TaC+5CO↑.
[0025] Although different pore structure regions have different pore structures, their tantalum-containing raw material and carbon source ratios are basically the same, thus reducing the difference in reaction shrinkage between different pore structure regions. Under high temperature conditions, partial sintering and neck connection occur between adjacent tantalum carbide particles, forming a continuous integrated tantalum carbide framework between different pore structure regions (including the interface transition zone and the adjacent region).
[0026] S600: The semi-finished product after carbothermal reduction sintering is mechanically processed, cleaned and purified to obtain gradient-pore porous tantalum carbide ceramic.
[0027] Machining includes processing the outer circle, end face, inner hole, or mounting steps of ceramic components to ensure dimensional accuracy and installation stability; cleaning can be carried out by ultrasonic cleaning, gas purging, etc. to remove processing dust and surface impurities; purification treatment is used to reduce the content of impurities such as B, Al, Fe, Ca, and V to avoid contamination of silicon carbide single crystal growth.
[0028] The present invention also provides a gradient-pore porous tantalum carbide ceramic prepared by the above method. The gradient-pore porous tantalum carbide ceramic includes a macropore region, a transition pore region and a micropore region in sequence along the gas phase transport direction. The pore size and porosity of the macropore region, the transition pore region and the micropore region gradually decrease along the gas phase transport direction. Adjacent pore structure regions are sintered together to form a continuously connected tantalum carbide skeleton.
[0029] The preferred hole structures for each hole structure region are as follows: Macropore region: The average pore size is 150-300μm, and the open porosity is 50%-70%, mainly used to reduce the resistance to gas passage; Transition pore region: The average pore size is 80-150μm, and the open porosity is 40%-60%. It is mainly used to mitigate the pore structure change between the large pore region and the small pore region. Small pore region: The average pore size is 20-80μm, and the open porosity is 25%-45%. It is mainly used to block particles and disperse and homogenize gas phase components. When the gradient-pore porous tantalum carbide ceramic is installed in a silicon carbide single crystal PVT growth furnace, the large pore area faces the silicon carbide powder source, and the small pore area faces the silicon carbide seed crystal. During the PVT growth process, the gas phase components generated by the sublimation of silicon carbide powder pass through the large pore area (low resistance gas inlet), the transition pore area (slow flow homogenization), and the small pore area (filtration and blocking) in sequence before entering the silicon carbide seed crystal growth area.
[0030] Compared with existing technologies, this invention sets up a large-pore region, a transition pore region, and a small-pore region with successively decreasing pore size and porosity along the gas phase transport direction. The large-pore region effectively reduces gas entry resistance, the small-pore region efficiently blocks SiC dust and particles, and the transition pore region achieves a smooth transition in pore size and porosity, thus balancing low gas flow resistance and high particle filtration capability. At the same time, the gradient distribution of pore size and porosity allows the gas phase components to be gradually dispersed and homogenized during the passage of the porous component, effectively improving the uniformity of gas phase component distribution on the seed crystal surface. In addition, by setting mixed transition materials between adjacent pore structure regions and combining integral pressing and integrated sintering to form a continuously connected tantalum carbide skeleton, the interlayer shrinkage difference and abrupt pore structure changes are significantly reduced, avoiding delamination, warping, and cracking, and improving the integrity and high-temperature structural stability of the component. This preparation method does not require complex templates or multiple independent sinterings, the process is simple and flexible, and can be customized for different PVT furnace sizes and process requirements, making it suitable for long-term service in high-temperature silicon-containing atmospheres. Attached Figure Description
[0031] Figure 1 This is a flowchart of the preparation method of gradient-pore porous tantalum carbide ceramics for silicon carbide single crystal growth in this invention; Figure 2This is a schematic diagram of the gradient-pore porous tantalum carbide ceramic used for silicon carbide single crystal growth in this invention. Figure 3 This is a schematic diagram of the partitioned filler and interface transition structure for different pore structures in this invention; Figure 4 This is a schematic diagram of the installation of gradient-pore porous tantalum carbide ceramic in a silicon carbide single-crystal PVT growth furnace according to the present invention. Detailed Implementation
[0032] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way.
[0033] Example 1 like Figures 1-4 As shown, this embodiment provides a method for preparing gradient-pore porous tantalum carbide ceramics for silicon carbide single crystal growth, the method comprising the following steps: S100. Using tantalum pentoxide powder as the tantalum source and carbon powder as the carbon source, pore-forming agents of different particle sizes and amounts are added to prepare mixtures with at least three different pore structure regions. As the pore size of different pore structure regions decreases, the particle size and amount of the corresponding pore-forming agent decrease sequentially. Specifically, tantalum pentoxide powder with a purity greater than 99.5% and an average particle size of 1-3 μm is selected as the tantalum source, and carbon powder with a purity greater than 99.9% and an average particle size of 15 μm is selected as the carbon source. The materials are prepared according to a molar ratio of tantalum pentoxide to carbon of 1:7. Each 100g of reaction material includes tantalum pentoxide powder and carbon powder; and macroporous region mixtures, transitional pore region mixtures, and microporous region mixtures are prepared separately, wherein: Macroporous zone mixture: Add PMMA pore-forming agent with a particle size of 100μm, the addition amount is 25% of the total mass of tantalum pentoxide and carbon powder; Transition pore zone mixture: Add PMMA pore-forming agent with a particle size of 50μm, the addition amount is 15% of the total mass of tantalum pentoxide and carbon powder; Small-pore zone mixture: Add PMMA pore-forming agent with a particle size of 10μm, the addition amount is 5% of the total mass of tantalum pentoxide and carbon powder; Each mixture was ball-milled in anhydrous ethanol for 6 hours, dried, and then passed through a 100-mesh sieve to obtain the mixtures of three different pore structure regions.
[0034] S200. Mix the mixtures of two adjacent pore structure regions at a mass ratio of 1:3 to 3:1 to obtain multiple interface transition materials. Specifically, mix the mixture of the large pore region and the mixture of the transition pore region at a mass ratio of 1:3 to obtain the first interface transition material; mix the mixture of the transition pore region and the mixture of the small pore region at a mass ratio of 1:3 to obtain the second interface transition material.
[0035] S300. Following the decreasing order of pore size in different pore structure regions, the mixture and interface transition material are sequentially filled into the same forming mold. The mixture filled into the forming mold is then subjected to unidirectional pre-pressing and cold isostatic pressing to form an integrated gradient pore blank. Different interface transition materials are located between the mixtures of two adjacent pore structure regions. Specifically, in a 160mm diameter circular mold, the following are filled in from bottom to top: large pore region mixture, first interface transition material, transition pore region mixture, second interface transition material, and small pore region mixture. The thickness of each filling region accounts for 35%, 5%, 20%, 5%, and 35% of the total blank thickness, respectively. After each mixture is filled, a light pre-pressing is performed at 3MPa. After all filling is complete, unidirectional pressing is performed at 20MPa for 5 minutes, followed by cold isostatic pressing at 100MPa for 10 minutes to obtain the integrated gradient pore blank.
[0036] S400. Degrease the gradient pore preform in a vacuum or inert atmosphere to decompose and remove the pore-forming agent and organic additives. Specifically, place the gradient pore preform in an argon atmosphere furnace and heat it to 400°C at a heating rate of 0.5°C / min, hold it at that temperature for 4 hours, so that the PMMA pore-forming agent is gradually decomposed and removed.
[0037] S500. Under vacuum or flowing argon conditions, the degreased gradient hole blank is subjected to carbothermic reduction sintering. Specifically, after degreasing, the furnace pressure is controlled at 500 Pa, high-purity argon is continuously introduced, and the temperature is raised to 1200℃ at a heating rate of 5℃ / min and held for 1 hour; then the temperature is further raised to 1700℃ and held for 5 hours, so that tantalum pentoxide and carbon can fully undergo carbothermic reduction reaction to generate tantalum carbide. After sintering, the blank is cooled with the furnace under argon protection.
[0038] S600: After the semi-finished product is subjected to carbothermal reduction sintering, it is machined, cleaned and purified to obtain a gradient-pore porous tantalum carbide ceramic disc of the required size.
[0039] The gradient-pore porous tantalum carbide ceramic disc prepared in Example 1 consists of a macropore region, a transition pore region, and a micropore region from bottom to top. The average pore diameter of the macropore region is about 150 μm and the open porosity is about 50%; the average pore diameter of the transition pore region is about 80 μm and the open porosity is about 40%; and the average pore diameter of the micropore region is about 20 μm and the open porosity is about 25%.
[0040] Example 2 The difference between Example 2 and Example 1 is as follows: In step S100, the average particle size of tantalum pentoxide is 1-3 μm, and the molar ratio of tantalum pentoxide to carbon is 1:10. Macroporous zone mixture: PMMA pore-forming agent with a particle size of 400μm is added, and the amount added is 40% of the total mass of tantalum pentoxide and carbon powder; Transition pore zone mixture: Add PMMA pore-forming agent with a particle size of 200μm, the addition amount is 30% of the total mass of tantalum pentoxide and carbon powder; Small pore area mixture: Add PMMA pore-forming agent with a particle size of 100μm, the amount of which is 20% of the total mass of tantalum pentoxide and carbon powder.
[0041] Each group of raw materials was added to anhydrous ethanol and ball-milled for 8 hours.
[0042] In step S200, the mixture of the large pore region and the mixture of the transition pore region are mixed at a mass ratio of 3:1 to obtain the first interface transition material; the mixture of the transition pore region and the mixture of the small pore region are mixed at a mass ratio of 3:1 to obtain the second interface transition material. In step S300, the thickness of each filler region in the forming mold accounts for 25%, 15%, 20%, 15%, and 25% of the total thickness of the blank, respectively. After each type of mixture is filled, a light pre-compression is performed at 8 MPa. After all the fillers are filled, a unidirectional pressing is performed at 80 MPa for 10 minutes, followed by cold isostatic pressing at 250 MPa for 20 minutes to obtain an integrated gradient hole blank.
[0043] In step S400, the temperature is increased to 600℃ at a heating rate of 3℃ / min and held for 1 hour.
[0044] In step S500, the furnace pressure is controlled at 5000Pa, and the temperature is increased to 1200℃ at a heating rate of 5℃ / min and held for 1 hour; then the temperature is increased to 2100℃.
[0045] The gradient-pore porous tantalum carbide ceramic disc prepared in Example 2 exhibits a gradient pore structure along its thickness direction, consisting of a macropore region, a transition pore region, and a micropore region from bottom to top. Testing revealed that the average pore diameter of the macropore region is approximately 300 μm, with an open porosity of approximately 70%; the average pore diameter of the transition pore region is approximately 150 μm, with an open porosity of approximately 60%; and the average pore diameter of the micropore region is approximately 80 μm, with an open porosity of approximately 45%.
[0046] Example 3 The difference between Example 3 and Example 1 is as follows: In step S100, the average particle size of tantalum pentoxide is 1-3 μm, and the molar ratio of tantalum pentoxide to carbon is 1:8.
[0047] Macroporous zone mixture: PMMA pore-forming agent with a particle size of 250μm is added, and the amount added is 32% of the total mass of tantalum pentoxide and carbon powder; Transition pore zone mixture: PMMA pore-forming agent with a particle size of 125μm is added, and the addition amount is 22% of the total mass of tantalum pentoxide and carbon powder; Small pore area mixture: Add PMMA pore-forming agent with a particle size of 55μm, the amount of which is 12% of the total mass of tantalum pentoxide and carbon powder.
[0048] In step S200, the mixture of the large pore area and the mixture of the transition pore area are mixed at a mass ratio of 1:1 to obtain the first interface transition material; the mixture of the transition pore area and the mixture of the small pore area are mixed at a mass ratio of 1:1 to obtain the second interface transition material.
[0049] In step S300, the thickness of each filling region in the circular mold accounts for 30%, 10%, 20%, 10%, and 30% of the total thickness of the gradient hole blank, respectively. After each type of mixture is filled, a light pre-compression is performed at 5 MPa. After all the filling is completed, a unidirectional pressing is performed at 50 MPa for 5 minutes, followed by cold isostatic pressing at 150 MPa for 10 minutes to obtain an integrated gradient hole blank.
[0050] In step S400, the temperature is increased to 450°C at a heating rate of 2°C / min and held for 2 hours.
[0051] In step S500, the furnace pressure is controlled at 1000 Pa, and the temperature is increased to 1200℃ at a heating rate of 5℃ / min and held for 1 hour; then the temperature is increased to 1927℃ and held for 2 hours.
[0052] The gradient-pore porous tantalum carbide ceramic disc prepared in Example 3 consists of a macropore region, a transition pore region, and a micropore region from bottom to top. The average pore diameter of the macropore region is about 220 μm and the open porosity is about 60%; the average pore diameter of the transition pore region is about 115 μm and the open porosity is about 50%; and the average pore diameter of the micropore region is about 50 μm and the open porosity is about 35%.
[0053] Example 4 The difference between Example 4 and Example 3 is as follows: In step S300, the proportions of the thickness of each filler region in the circular mold to the total thickness of the blank are as follows: 35% for the large hole region, 5% for the first interface transition region, 20% for the transition hole region, 5% for the second interface transition region, and 35% for the small hole region. Among them, the thickness of the first interface transition region accounts for 25% of the thickness of the transition hole region, and the thickness of the second interface transition region accounts for 25% of the thickness of the transition hole region.
[0054] The gradient-pore porous tantalum carbide ceramic disc prepared in Example 4 consists of a large pore region, a transition pore region, and a small pore region from bottom to top. Upon inspection, no obvious layering interface was observed between the pore structure regions. The interface transition region is relatively thin but sufficient to achieve interlacing connection of particles between adjacent pore structure regions.
[0055] Example 5 The difference between Example 5 and Example 3 is as follows: In step S300, the proportions of the thickness of each filler region in the circular mold to the total thickness of the blank are as follows: 25% for the large hole region, 15% for the first interface transition region, 25% for the transition hole region, 15% for the second interface transition region, and 20% for the small hole region. Among them, the thickness of the first interface transition region accounts for 60% of the thickness of the transition hole region, and the thickness of the second interface transition region accounts for 60% of the thickness of the transition hole region.
[0056] The gradient-pore porous tantalum carbide ceramic disc prepared in Example 5 consists of a large pore region, a transition pore region, and a small pore region from bottom to top. Upon inspection, no obvious layering interface was observed between the pore structure regions. The interface transition region has sufficient thickness of mixed powder, which can effectively mitigate the abrupt changes and shrinkage differences in pore structure between adjacent pore structure regions.
[0057] Example 6 The difference between Example 6 and Example 3 is as follows: In step S300, the proportions of the thickness of each filler region in the circular mold to the total thickness of the blank are as follows: 30% for the large hole region, 10% for the first interface transition region, 20% for the transition hole region, 10% for the second interface transition region, and 30% for the small hole region. Among them, the thickness of the first interface transition region accounts for 50% of the thickness of the transition hole region, and the thickness of the second interface transition region accounts for 50% of the thickness of the transition hole region.
[0058] The gradient-pore porous tantalum carbide ceramic disc prepared in Example 6 consists of a macropore region, a transition pore region, and a micropore region from bottom to top. No obvious delamination interfaces are observed between the pore structure regions, and the pore size and porosity of the interface regions gradually change. The filler thickness ratio in Example 6 ensures that the interface transition region has sufficient mixed powder thickness while retaining the effective thickness of the transition pore region itself, allowing the transition pore region to continue to play its role in mitigating airflow resistance and connecting the macropore and micropore regions.
[0059] Example 7 The difference between Example 7 and Example 3 is as follows: In step S400, the temperature is increased to 400℃ at a heating rate of 0.5℃ / min and held for 4 hours.
[0060] The gradient-pore porous tantalum carbide ceramic disc prepared in Example 7 consists of a large pore region, a transition pore region, and a small pore region from bottom to top. No obvious layering interface is observed between the pore structure regions, and the degreasing process is stable, with the pore-forming agent completely decomposed and discharged.
[0061] Example 8 The difference between Example 8 and Example 3 is as follows: In step S400, the temperature is increased to 600℃ at a heating rate of 3℃ / min and held for 1 hour.
[0062] The gradient-pore porous tantalum carbide ceramic disc prepared in Example 8 consists of a large pore region, a transition pore region, and a small pore region from bottom to top. No obvious layering interface is observed between the pore structure regions, and the pore-forming agent is completely decomposed.
[0063] Example 9 The difference between Example 9 and Example 3 is as follows: In step S500, the temperature is increased to 1200℃ at a heating rate of 5℃ / min and held for 1 hour; then the temperature is increased to 1700℃ and held for 5 hours.
[0064] Upon testing, it was found that in the gradient-pore porous tantalum carbide ceramic disc prepared in Example 9, tantalum pentoxide was basically converted into tantalum carbide, and a continuously connected porous tantalum carbide skeleton was formed between the pore structure regions.
[0065] Example 10 The difference between Example 10 and Example 3 is as follows: In step S500, the furnace pressure is controlled at 5000Pa, and the temperature is increased to 1200℃ at a heating rate of 5℃ / min and held for 1 hour; then the temperature is increased to 2100℃ and held for 1 hour.
[0066] Testing revealed that in the gradient-pore porous tantalum carbide ceramic disc prepared in Example 10, tantalum pentoxide was completely converted into tantalum carbide, and a continuous tantalum carbide skeleton with a firm connection was formed between the pore structure regions, maintaining a good pore structure.
[0067] Based on the description of the above embodiments, it can be seen that Example 1 uses the lower limit values of the pore-forming agent particle size and addition amount to obtain a gradient pore structure with lower limits of pore size and porosity; Example 2 uses the upper limit values to obtain a gradient pore structure with upper limits of pore size and porosity; Example 3 uses intermediate values to obtain a gradient pore structure with intermediate performance. These three examples collectively demonstrate that there is a clear correspondence between the pore-forming agent particle size and addition amount and the final pore size and porosity, and that the pore structure of each pore structure region can be precisely controlled by adjusting the pore-forming agent parameters.
[0068] Examples 4, 5, and 6 verified the lower limit, upper limit, and median value of the interface transition zone thickness range, respectively. The results show that the interface transition zone thickness can effectively achieve interlaced particle connection and integrated sintering in adjacent regions within the range of 5%–15% (accounting for the total thickness of the green body) and 25%–60% (accounting for the thickness of the transition hole region), with a ratio of 10% / 50% showing the best gradient transition effect.
[0069] Examples 7 and 8 verified the lower and upper limits of the degreasing process parameters, proving that the pore-forming agent can be completely decomposed and discharged within a heating rate of 0.5 to 3 °C / min and a temperature range of 400 to 600 °C without causing cracking or interlayer separation in the green body.
[0070] Examples 9 and 10 verified the lower and upper limits of the sintering temperature. The reaction at 1700℃ was relatively mild, requiring a longer time (5 hours) to achieve complete conversion; at 2100℃, the reaction rate was significantly increased, and conversion could be completed in 1 hour. Under both temperature conditions, gradient-pore porous tantalum carbide ceramics with tantalum carbide as the main phase and a continuous framework could be obtained.
[0071] In summary, the embodiments of the present invention can successfully prepare gradient-pore porous tantalum carbide ceramics under different parameter combinations. The TaC skeleton is formed by integrated sintering between the pore structure regions, without defects such as delamination and cracking. The pore size and porosity of each region show a regular gradient change with the change of pore-forming agent parameters, which fully proves the feasibility and stability of the technical solution of the present invention.
[0072] It should be noted that in step S100, a binder accounting for 1%-5% of the mass of the reaction raw materials can also be added together with the pore-forming agent to assist in molding, wherein the binder is PVA.
[0073] The foregoing provides a detailed description of a gradient-pore porous tantalum carbide ceramic for silicon carbide single crystal growth and its preparation method. Specific examples have been used to illustrate the principles and implementation methods of this application; the descriptions of the embodiments are merely for the purpose of helping to understand the core ideas of this application. It should be noted that those skilled in the art can make various improvements and modifications to this application without departing from its principles, and these improvements and modifications also fall within the protection scope of the claims of this application.
Claims
1. A method for preparing gradient-pore porous tantalum carbide ceramics for silicon carbide single crystal growth, characterized in that, The method includes the following steps: S100. Using tantalum pentoxide powder as the tantalum source and carbon powder as the carbon source, pore-forming agents with different particle sizes and different amounts are added to prepare a mixture of at least three different pore structure regions. As the pore size of different pore structure regions decreases, the particle size and amount of the pore-forming agent added decrease sequentially. S200: Mix the mixtures of two adjacent pore structure regions at a mass ratio of 1:3 to 3:1 to obtain multiple interface transition materials; S300. According to the decreasing order of pore size in different pore structure regions, the mixture and interface transition material are sequentially filled into the same molding die, and the mixture filled into the molding die is sequentially subjected to unidirectional pre-pressing and cold isostatic pressing to form an integrated gradient pore blank, wherein the different interface transition materials are located between the mixtures of two corresponding adjacent pore structure regions. S400: Degrease the gradient pore preform in a vacuum or inert atmosphere to decompose and remove the pore-forming agent and organic additives. S500. Under vacuum or flowing argon conditions, the degreased gradient pore blank is subjected to carbothermic reduction sintering treatment, so that tantalum pentoxide in the mixture reacts with carbon to generate tantalum carbide, thereby forming a continuously connected porous tantalum carbide skeleton between different pore structure regions, and obtaining a semi-finished product. S600: The semi-finished product after carbothermal reduction sintering is mechanically processed, cleaned and purified to obtain gradient-pore porous tantalum carbide ceramic.
2. The method for preparing gradient-pore porous tantalum carbide ceramics for silicon carbide single crystal growth according to claim 1, characterized in that, In step S100, the pore structure region includes a macropore region, a transition pore region, and a micropore region with successively decreasing pore sizes, and the molar ratio of tantalum pentoxide to carbon in the mixture is 1:7-1:
10.
3. The method for preparing gradient-pore porous tantalum carbide ceramics for silicon carbide single crystal growth according to claim 2, characterized in that, The pore-forming agent is one or more selected from PMMA microspheres, polystyrene microspheres, starch, and phenolic resin microspheres, wherein: The pore size of the pore-forming agent in the macroporous region of the mixture is 100-400 μm, and the amount of pore-forming agent added is 25%-40% of the total mass of tantalum pentoxide powder and carbon powder in the mixture. The transition pore zone corresponds to a pore-forming agent particle size of 50-200μm in the mixture, and the amount of pore-forming agent added is 15%-30% of the total mass of tantalum pentoxide powder and carbon powder in the corresponding mixture; The pore size of the pore-forming agent in the mixture corresponds to a particle size of 10-100μm, and the amount of pore-forming agent added is 5%-20% of the total mass of tantalum pentoxide powder and carbon powder in the mixture.
4. The method for preparing gradient-pore porous tantalum carbide ceramics for silicon carbide single crystal growth according to claim 1, characterized in that, The specific steps of S300 are as follows: Following the decreasing order of pore size in different pore structure regions, the mixture and interface transition material are sequentially filled into the same molding die. After the filling is completed, the overall unidirectional pre-pressing and cold isostatic pressing are performed sequentially to form an integrated gradient pore blank. Alternatively, according to the decreasing pore size of different pore structure regions, the mixture and interface transition material are sequentially filled into the same molding die, and unidirectional pre-pressing is performed after each mixture or interface transition material is filled into the molding die, until all filling is completed. Then, overall unidirectional pre-pressing and cold isostatic pressing are performed sequentially to form an integrated gradient pore blank. The unidirectional pre-compression pressure is 20-80 MPa, and the cold isostatic pressure is 100-250 MPa.
5. The method for preparing gradient-pore porous tantalum carbide ceramics for silicon carbide single crystal growth according to claim 1, characterized in that, In step S400, the heating rate for degreasing is 0.5-3℃ / min, the degreasing temperature is 400-600℃, and the holding time is 1-4h.
6. The method for preparing gradient-pore porous tantalum carbide ceramics for silicon carbide single crystal growth according to claim 1, characterized in that, In step S500, the carbothermic reduction sintering temperature is 1700-2100℃, the holding time is 1-5h, and the pressure is 500-5000Pa.
7. The method for preparing gradient-pore porous tantalum carbide ceramics for silicon carbide single crystal growth according to claim 1, characterized in that, The toner is one or more of carbon black, graphite powder, or high-purity toner.
8. The method for preparing gradient-pore porous tantalum carbide ceramics for silicon carbide single crystal growth according to claim 3, characterized in that, In step S300, the filler thickness of a single interface transition material accounts for 5%-15% of the total thickness of the gradient hole blank, and the filler thickness of a single interface transition material accounts for 25%-60% of the thickness of the transition hole region.
9. A gradient-pore porous tantalum carbide ceramic for silicon carbide single crystal growth, characterized in that, The ceramic is prepared according to any one of claims 1 to 8, which is a gradient-pore porous tantalum carbide ceramic for silicon carbide single crystal growth, wherein: The gradient-pore porous tantalum carbide ceramic includes a macropore region, a transition pore region and a micropore region along the gas phase transport direction. The pore size and porosity of the macropore region, the transition pore region and the micropore region gradually decrease along the gas phase transport direction. Adjacent pore structure regions are connected to form a continuous tantalum carbide skeleton through integrated sintering. When this gradient-pore porous tantalum carbide ceramic is installed in a silicon carbide single-crystal PVT growth furnace, the large pore area faces the silicon carbide powder source, and the small pore area faces the silicon carbide seed crystal.
10. The gradient-pore porous tantalum carbide ceramic for silicon carbide single crystal growth according to claim 9, characterized in that, The average pore size of the macropore region is 150-300 μm, and the open porosity is 50%-70%; the average pore size of the transition pore region is 80-150 μm, and the open porosity is 40%-60%; the average pore size of the micropore region is 20-80 μm, and the open porosity is 25%-45%.
Citation Information
Patent Citations
Preparation method of porous ceramic material with gradient structure
CN107673760A
A porous ultra-high temperature carbide ceramic with high strength and stepped pore size distribution and its preparation method
CN120441340B
Gradient sintering preparation method and application of porous tantalum carbide plate
CN121318523A